Institutional Ownership Moderate Tax Avoidance And Agency Costs Effect On Company Value - Nurhayati nurhayati (Universitas Islam Lamongan, 2022)
Tax Avoidance may Increases Company Value. However, Tax Avoidance Causes Agency Costs which Reduce Company Value. Both are Moderated by Institutional Ownership to Prevent Losses. I Want to Prove This Moderation. CETR Measures Tax Avoidance, STA Measures Agency Costs, Tobins Q Measures Company Value, and INST Measures Institutional Ownerships. Population is Consumer Goods Manufacturing Companies Listed in Indonesian Stock Exchange from 2016 - 2020. 69 Samples is Selected with Purposive Sampling and Analyzed with WarpPLS 5.0 Resulting; Tax Avoidance have Highly Significant Positive Effect on Company Value, Agency Costs have Significant Negative Effect on Company Value, Institutional Ownership cannot Moderate Relationship Between Tax Avoidance and Company Value, but It have Significant Negative Moderation Effect to Agency Costs and Company Value.